Influence of MHD Turbulence on Ion Kappa Distributions in the Earth's Plasma Sheet as a Function of Plasma β Parameter - Eyelade, A. V.; Espinoza, C. M.; Stepanova, M.; Antonova, E. E.; Ovchinnikov, I. L.; Kirpichev, I. P. (Frontiers in Astronomy and Space Sciences, 2021)
The possible influence of MHD turbulence on the energy distributions of ions in the Earth’s plasma sheet was studied using data taken by the THEMIS satellites. Turbulence levels were traced using eddy diffusion coefficients (D), of which we measured one for each Geocentric Solar Magnetospheric (GSM) coordinates every 12 minutes. Ion fluxes between 1.75 and 210,5 keV during the same time windows that correspond to mainly suprathermal populations were fitted to kappa distribution functions, which approximate a Maxwellian distribution when the kappa-index is large. We found that the distribution of the eddy diffusion coefficients is bimodal, independently of both the eddy diffusion component and the plasma beta parameter, which is defined as the ratio between plasma and magnetic pressures. The main peak corresponds to turbulent plasma flows with D>10^3 km^2 s^{-1}. In such cases, the impact of turbulence on the kappa index depends on the value of beta and also on the direction of the turbulent transport. For eddy diffusion perpendicular to the neutral sheet, the values of kappa decrease as Dzz increases for beta<2; while for higher values of beta, kappa increases with Dzz. For the other two directions, the values of kappa decrease as D increases. This last tendency is stronger for beta approx 1 but almost null for beta approx 10. The secondary peak in the distribution of D values might represent quasi-laminar flows forming part of very large vortices, correct detection and description of which is beyond the scope of this study.